2006
DOI: 10.1074/jbc.m602297200
|View full text |Cite
|
Sign up to set email alerts
|

Dinucleotide Spore Photoproduct, a Minimal Substrate of the DNA Repair Spore Photoproduct Lyase Enzyme from Bacillus subtilis

Abstract: The overwhelming majority of DNA photoproducts in UVirradiated spores is a unique thymine dimer called spore photoproduct (SP, 5-thymine-5,6-dihydrothymine). This lesion is repaired by the spore photoproduct lyase (SP lyase) enzyme that directly reverts SP to two unmodified thymines. The SP lyase is an S-adenosylmethionine-dependent iron-sulfur protein that belongs to the radical S-adenosylmethionine superfamily. In this study, by using a well characterized preparation of the SP lyase enzyme from Bacillus subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
88
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 37 publications
13
88
1
1
Order By: Relevance
“…The insertion of a cysteine residue inside the mutated enzyme active-site thus completely restored the SP lyase repair activity. Furthermore, kinetic experiments revealed that, while the wild-type SP lyase had a DNA repair rate of 1.66 nmol min À1 mg À1 (in the range of the reported values for SP lyases 5,12 ), the double mutant proved to be more than two-times faster (3.48 nmol min À1 mg À1 ) (Fig. 2).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The insertion of a cysteine residue inside the mutated enzyme active-site thus completely restored the SP lyase repair activity. Furthermore, kinetic experiments revealed that, while the wild-type SP lyase had a DNA repair rate of 1.66 nmol min À1 mg À1 (in the range of the reported values for SP lyases 5,12 ), the double mutant proved to be more than two-times faster (3.48 nmol min À1 mg À1 ) (Fig. 2).…”
mentioning
confidence: 79%
“…Several SP lyases from Bacilli 7,12,15,16 and one from Clostridia 9 have been biochemically characterized. However, it was not clear so far how the repair activity takes place in Clostridia as the crucial cysteine residue found in Bacilli (C140 in Gt) is not conserved among clostridial SP lyases.…”
Section: View Article Onlinementioning
confidence: 99%
“…At each time point (0, 15 30, 60, 120, 215, and 280 min) 20 l and 10 l of the solution were transferred into Eppendorf tubes, and the reaction was stopped by flash-freezing in liquid nitrogen. Conversion of the spore photoproduct (SPTpT) into the unmodified dinucleoside monophosphate (TpT) and other products in SPL-treated samples was quantified by HPLC coupled to tandem mass spectrometry (HPLC-MS/MS), using the same conditions as for samples treated by wt SPL (7).…”
Section: Methodsmentioning
confidence: 99%
“…Iron and Sulfide Binding to WT and C141A B. subtilis SPL-[Fe-S] cluster reconstitutions of wt and C141A B. subtilis SPL were carried out under strictly anaerobic conditions in a glove box containing Ͻ2 ppm O 2 as previously described (7).…”
Section: Methodsmentioning
confidence: 99%
“…Removal For enzymatic assays the SP-containing DNA and the SP dinucleotide are normally produced via irradiation of dried oligonucleotides together with dipicolinic acid (DPA). 5,14,16,[46][47][48][49] However, in order to obtain defined nucleotide sequences, necessary for many applications such as crystallization, this method is limited to short oligonucleotides and the yields are very unsatisfactory.…”
Section: The Spore Photoproductmentioning
confidence: 99%